Implementation Of Strengthening Political Education Through Pancasila Education In Classrooms At Sayyid Yusuf High School, Talango District, Sumenep Regency - Iqwan Homaidy; Sunarso Sunarso (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the implementation of political education through Pancasila Education and its contribution to strengthening students' political understanding at Sayyid Yusuf High School in Talango District, Sumenep Regency. The research employed a qualitative case study design involving the school principal, Pancasila Education teacher, and students selected through purposive sampling. Data were collected through semi structured interviews, classroom observations, and document analysis, and were analyzed using an interactive qualitative approach. The findings reveal that political education was integrated into learning activities related to democracy, citizenship rights and obligations, governmental systems, and political participation. The implementation was supported by classroom discussions, democratic simulations, and school based civic activities that provided students with practical democratic experiences. Students demonstrated improvement in democratic knowledge, civic responsibility, political participation awareness, confidence in expressing opinions, and concern for social issues. Several challenges were identified, including limited access to technology, geographic constraints associated with island conditions, varying levels of political literacy, and exposure to digital misinformation. The study highlights the importance of contextual civic learning, digital literacy strengthening, and institutional support in fostering democratic citizenship and political resilience among secondary school students.